Biomarkers in acute respiratory distress syndrome. Issue 1 (February 2021) - Jabaudon, Matthieu; Blondonnet, Raiko; Ware, Lorraine B.
Abstract : Purpose of review: This article provides an overview of protein biomarkers for acute respiratory distress syndrome (ARDS) and their potential use in future clinical trials. Recent findings: The protein biomarkers studied as indices of biological processes involved in the pathogenesis of ARDS may have diagnostic and/or prognostic value. Recently, they also proved useful for identifying ARDS phenotypes and assessing heterogeneity of treatment effect in retrospective analyses of completed clinical trials. Summary: This article summarizes the current research on ARDS biomarkers and provides insights into how they should be integrated as prognostic and predictive enrichment tools in future clinical trials.